Mind the Depth: Visual Perception of Shapes Is Better in Peripersonal Space. (November 2018) - Blini, Elvio; Desoche, Clément; Salemme, Romeo; Kabil, Alexandre; Hadj-Bouziane, Fadila; Farnè, Alessandro
Closer objects are invariably perceived as bigger than farther ones and are therefore easier to detect and discriminate. This is so deeply grounded in our daily experience that no question has been raised as to whether the advantage for near objects depends on other features (e.g., depth itself). In a series of five experiments ( N = 114), we exploited immersive virtual environments and visual illusions (i.e., Ponzo) to probe humans' perceptual abilities in depth and, specifically, in the space closely surrounding our body, termed peripersonal space. We reversed the natural distance scaling of size in favor of the farther object, which thus appeared bigger, to demonstrate a persistent shape-discrimination advantage for close objects. Psychophysical modeling further suggested a sigmoidal trend for this benefit, mirroring that found for multisensory estimates of peripersonal space. We argue that depth is a fundamental, yet overlooked, dimension of human perception and that future studies in vision and perception should be depth aware.